Organisational and economic aspects of the archives digitalisation of the State Film Fund of the Russian Federation - M. I. Kosinova; A. A. Gasilina (Вестник университета)
The object of the study is the State Film Fund of the Russian Federation; the subject is the project for the global digitisation of the State Film Fund’s film archives, launched at the end of 2018 and currently underway. The aim of the study is to analyse the State Film Fund’s digitisation project and to identify possible problems that may arise during its implementation. Research objectives are staff shortages problem analysis and the project’s socio-cultural and economic efficiency analysis. The study used the following methods: historical and genetic analysis, descriptive analysis of literature and media materials, qualitative content analysis of documents, reports and other materials, comparative analysis, secondary analysis of public opinion surveys and statistical data. The developed project of an educational portal can be practically implemented on the basis of the State Film Fund.